2020
DOI: 10.1007/s00262-020-02718-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint-related serum proteins and genetic variants predict outcomes of localized prostate cancer, a cohort study

Abstract: Background The clinical predictors and biological mechanisms for localized prostate cancer (PCa) outcomes remain mostly unknown. We aim to evaluate the role of serum immune-checkpoint-related (ICK) proteins and genetic variations in predicting outcomes of localized PCa. Methods We profiled the serum levels of 14 ICK-related proteins (BTLA, GITR, HVEM, IDO, LAG-3, PD-1, PD-L1, PD-L2, Tim-3, CD28, CD80, 4-1BB, CD27, and CTLA-4) in 190 patients with localized PCa. The genotypes of 97 single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 31 publications
2
51
0
1
Order By: Relevance
“…Upon engagement, HVEM provides pro-survival and proliferative signals through activation of NF-kB transcriptional pathways, whereas BTLA negatively regulates T cell-mediated responses [ 36 , 37 , 38 , 39 ]. Further, aberrant surface expression and levels of soluble BTLA (sBTLA) in sera have been related to prognosis in various solid tumors and hematological malignancies [ 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. BTLA blockade, alone or in combination with chemotherapy, led to improved survival in epithelial ovarian carcinoma murine models [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upon engagement, HVEM provides pro-survival and proliferative signals through activation of NF-kB transcriptional pathways, whereas BTLA negatively regulates T cell-mediated responses [ 36 , 37 , 38 , 39 ]. Further, aberrant surface expression and levels of soluble BTLA (sBTLA) in sera have been related to prognosis in various solid tumors and hematological malignancies [ 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. BTLA blockade, alone or in combination with chemotherapy, led to improved survival in epithelial ovarian carcinoma murine models [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of HVEM in T cell activation is well established, the role of HVEM expressed by tumor cells on the immune system is not clear. Several clinical studies have shown that HVEM expression is upregulated in many types of cancers including colorectal cancers [ 16 ], melanomas [ 17 ], esophageal carcinomas [ 18 ], gastric cancers [ 19 ], hepatocarcinomas [ 20 ], breast cancers [ 21 ], lymphomas [ 22 ], and PCa [ 23 ]. In these studies, a worse prognosis and lower survival of patients correlated with high levels of HVEM expression in the tumors or with elevated detection of soluble HVEM in the serum.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, upregulated expression of BTLA on CD8 + or CD4 + T cells or increased levels of soluble BTLA were associated with unfavorable prognosis for gallbladder cancer [ 26 ], diffuse large-B cell lymphoma [ 27 ], clear cell renal cell cancer [ 27 ], and prostate cancer patients [ 23 ]. Moreover, we have shown that tumor-specific CD8 + T cells are inhibited in melanoma patients through HVEM/BTLA signaling [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, up regulated expression of BTLA on CD8 + or CD4 + T cells or increased levels of soluble BTLA were associated to unfavorable prognosis for gallbladder cancer [23], diffuse large-B cell lymphoma [24], clear cell renal cell cancer [24] and prostate cancer patients [20]. Moreover, we have shown that tumor-specific CD8 + T cells are inhibited in melanoma patients through HVEM/BTLA signaling [25].…”
Section: Introductionmentioning
confidence: 71%
“…Although the role of HVEM on T cell activation is well established, much less is known on the role of HVEM expressed by tumor cells on the immune system. Several clinical studies have shown that HVEM expression is up regulated in many types of cancers including colorectal cancers [13], melanomas [14], esophageal carcinomas [15], gastric cancers [16], hepatocarcinomas [17], breast cancers [18], lymphomas [19] or PCa [20]. In these studies, high levels of HVEM expression by tumors or soluble HVEM in the sera were associated with a worse prognosis and lower survival.…”
Section: Introductionmentioning
confidence: 99%